Waardenburg Syndrome Type 1 in an Infant Diagnosed with Congenital Hypothyroidism - Dayasiri, Kavinda Chandimal; Perera, Chamila; Bandara, Wasana; Ranasinghe, Jagath (Journal of Nepal Paediatric Society, 2019)
Waardenburg syndrome type 1 is a rare autosomal dominant auditory-pigmentary syndrome characterised by pigmentary abnormalities of the hair, skin, and eyes associated with congenital non-progressive sensorineural hearing loss. Diagnosis is usually clinical and based on the characteristic clinical features which constitute major and minor criteria. Though hypothyroidism has been described among family members of children with Waardenburg syndrome type 1 there is no reported existence of the two conditions in the same patient. Here we report Waardenburg Syndrome Type 1 in an infant who was already diagnosed to have congenital hypothyroidism and whether it would be a co incidental finding or an association needs further evaluation.